Peningkatan Kemampuan Matematika Siswa Sekolah Dasar Melalui Media Pembelajaran Ular Tangga Aljabar - Mustika Fitri Larasati Sibuea; Hommy Dorthy Ellyany Sinaga (Universitas Asahan, 2018)
AbstractThe purpose of this research is to find out whether by using algebra ladder snake learning media can improve students' math ability and can improve student learning activity. This research is a Classroom Action Research. The subject of this research is the third grade students of SD Tamansiswa Sukadamai of Asahan Regency, amounting to 30 students. And the object in this study is the use of learning media ladder algebra snake in improving students' math skills and student learning activeness. The instrument used in this research is the students' math test in the form of test essay and observation sheet. The average value of student activity observation observation cycle I and II is 2.6 and 3.9. Exhaustiveness of preliminary test was obtained at 23.33%. After learning by using algebra ladder learning medium, there was an increase in the students' mathematics ability test of cycles I and II of 62.33% and 93.33%. It can be concluded that learning using algebra stepping snake learning media can improve the mathematics ability of elementary school students. Keywords: mathematical ability, learning activity, learning media of algebra ladder snake AbstrakTujuan penelitian ini adalah untuk mengetahui apakah dengan menggunakan media pembelajaran ular tangga aljabar dapat meningkatkan kemampuan matematika siswa dan dapat meningkatkan keaktifan belajar siswa. Penelitian ini merupakan Penelitian Tindakan Kelas. Yang menjadi subjek dalam penelitian ini adalah siswa kelas III SD Tamansiswa Sukadamai Kabupaten Asahan yang berjumlah 30 siswa. Dan yang menjadi objek dalam penelitian ini adalah penggunaan media pembelajaran ular tangga aljabar dalam meningkatkan kemampuan matematika siswa dan keaktifan belajar siswa. Instrumen yang digunakan dalam penelitian ini adalah tes kemampuan matematika siswa dalam bentuk essay tes dan lembar observasi. Nilai rata-rata hasil observasi keaktifan siswa siklus I dan II sebesar 2,6 dan 3,9. Ketuntasan belajar tes awal diperoleh sebesar 23,33%. Setelah dilakukan pembelajaran dengan menggunakan media pembelajaran ular tangga aljabar, terjadi peningkatan pada tes kemampuan matematika siswa siklus I dan II sebesar 62,33% dan 93,33%. Dapat disimpulkan bahwa pembelajaran menggunakan media pembelajaran ular tangga aljabar dapat meningkatkan kemampuan matematika siswa sekolah dasar. Kata kunci: kemampuan matematika, keaktifan belajar, media pembelajaran ular tangga aljabar